If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + 8m = 8(5m + -3) Reorder the terms: 40 + 8m = 8(-3 + 5m) 40 + 8m = (-3 * 8 + 5m * 8) 40 + 8m = (-24 + 40m) Solving 40 + 8m = -24 + 40m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-40m' to each side of the equation. 40 + 8m + -40m = -24 + 40m + -40m Combine like terms: 8m + -40m = -32m 40 + -32m = -24 + 40m + -40m Combine like terms: 40m + -40m = 0 40 + -32m = -24 + 0 40 + -32m = -24 Add '-40' to each side of the equation. 40 + -40 + -32m = -24 + -40 Combine like terms: 40 + -40 = 0 0 + -32m = -24 + -40 -32m = -24 + -40 Combine like terms: -24 + -40 = -64 -32m = -64 Divide each side by '-32'. m = 2 Simplifying m = 2
| 6m+4=6m+1 | | -7x-10=-3x-22 | | 10+3w=49 | | 10=1x+1 | | 5=2+1x | | 6b-24=2b+6(2b-4) | | (10x-2)+(3x+8)= | | 2/16=3/24 | | 1y-7=3 | | 9/5-7/2 | | 24+2x=y | | -8-4x=-7x-5 | | 8(4-3x)= | | -4-7n=6(n-5) | | 5W+12=162 | | 5(z+4)=35 | | 23+12x+15n-5x-4n-29= | | -2(X+2)+3X=2(X+1)+1 | | 1x+6=9 | | 7(4+4p)=28+5p | | 3=4t-9 | | D=BAC | | 3x-9=-25+X | | R+82=87 | | -2x+-12=6-8x | | 9x+x+11=3+8+10x | | -20+5x=110 | | -x-33=-4x-3 | | -8n+-4=-2+n-6-8n | | -5-4(2+4x)=-6x-13 | | 2(x-5)=x-7 | | 130/134 |